From fiction to fact: The impact of CEO social networks - Thomas Kirchmaier; Konstantinos Stathopoulos (The University of Manchester, Manchester Business School, 2008)
This paper investigates the relationship between a CEO's social network, firm identity, and firm performance. There are two competing theories that predict contradictory outcomes. Following social network theory, one would expect a positive relation between social networks and firm performance, while agency theory in general and Bebchuk's managerial power approach in particular predicts a negative relationship between social networks and firm performance. Based on a new and comprehensive measure of CEOs social networks, we observe for 363 non-financial firms in the UK that the size of a CEO's social network affects firm performance negatively. Even so, growth companies are actively seeking CEOs with a large social network, which is in line with the social network theory. Still, we find evidence in support of the argument that well-connected CEOs use the power they obtain through their social network to the detriment of shareholders.
Keywords: G34; L25; Z13; 330; CEO; boards of directors; social network; accounting performance; Führungskräfte; Netzwerk; Soziale Beziehungen; Unternehmensentwicklung; Großbritannien